DEVELOPING ESP READING COMPREHENSION INSTRUCTIONAL MATERIALS THROUGH SCHEMA THEORY APPROACH AT PAI STUDY PROGRAM OF TARBIYAH FACULTY OF IAIN BENGKULU - Syamsul Rizal (UAD TEFL International Conference)
The fact that the English reading comprehension ability of the students of Islamic Religious Education of Tarbiyah Faculty of IAIN Bengkulu is still low. One of the causes of the problem is the ineffectiveness of the English teaching materials that have been used. Therefore, the purpose of this study is to produce ESP English reading comprehension instructional materials based on Islamic Educational Studies (IES) in accordance with the characteristics of Islamic Education Study Program students of Tarbiyah Faculty. The procedure in developing this instructional materials was adapted from Borg and Gall's research and development model. The research method used to investigate the effectiveness of the product is quasi-experimental method.  The developed instructional material prototype was validated by material and media experts and also by English lecturers. According to experts of material and media, the product is very good with the percentage of ideality of 76% and 73.3%. According to the English lecturers’ validations are also categorized in good category with 77.5% percentage and the students' responses from the aspect of material, presentation and language assessment are classified as positive (good) category. There is a significant difference of reading comprehension achievement between experimental and control group students. It means that the students’ reading comprehension ability in the experimental group is higher than that of in the control group. It indicates that the product of this research is effective in improving the students’ English reading comprehension achievement.